DESKRIPSI KEMAMPUAN KOMUNIKASI MATEMATIS SISWA DALAM MENYELESAIKAN PERMASALAHAN SEGITIGA DAN SEGIEMPAT - Maharani, Desta; Ramlah, Ramlah (JPMI (Jurnal Pembelajaran Matematika Inovatif), 2021)
This study aims to describe the mathematical communication skills of junior high school students in solving triangular and quadrilateral problems. The qualitative descriptive method was used in collecting data on the results of the mathematical communication skills test, as well as the results of interviews with six class VIII student respondents in a junior high school in Karawang district. Data analysis was used through four stages, namely collecting data from tests and interviews, then categorizing and simplifying them. So that data can be obtained in accordance with the research objectives to get the right conclusions. The results of this study indicate that the students' mathematical communication skills on indicators of written texts and drawing of students are not able to solve problems according to procedures. Whereas in the mathematical expression indicator the students were able to solve the problem according to the procedure, but there were mistakes in answering the questions. Then it can be conclude that the level of student’s mathematical communication ability is still relatively low.